Optimized Camera-Based Patient Positioning in CT: Impact on Radiation Exposure - Manava, Panagiota; Galster, Marco; Ammon, Josefin; Singer, Julian; Lell, Michael; Rieger, Vera (Investigative Radiology, 2023)
Objective The aim of this study was to evaluate whether a 3-dimensional (3D) camera can outperform highly trained technicians in precision of patient positioning and whether this transforms into a reduction in patient exposure. Materials and Methods In a single-center study, 3118 patients underwent computer tomography (CT) scans of the chest and/or abdomen on a latest generation single-source CT scanner supported with an automated patient positioning system by 3D camera. One thousand five hundred fifty-seven patients were positioned laser-guided by a highly trained radiographer (camera off) and 1561 patients with 3D camera (camera on) guidance. Radiation parameters such as effective dose, organ doses, CT dose index, and dose length product were analyzed and compared. Isocenter accuracy and table height were evaluated between the 2 groups. Results Isocenter positioning was significantly improved with the 3D camera (P < 0.001) as compared with visual laser-guided positioning. Absolute table height differed significantly (P < 0.001), being higher with camera positioning (165.6 ± 16.2 mm) as compared with laser-guided positioning (170.0 ± 20.4 mm). Radiation exposure decreased using the 3D camera as indicated by dose length product (321.1 ± 266.6 mGy·cm; camera off: 342.0 ± 280.7 mGy·cm; P = 0.033), effective dose (3.3 ± 2.7 mSv; camera off: 3.5 ± 2.9; P = 0.053), and CT dose index (6.4 ± 4.3 mGy; camera off: 6.8 ± 4.6 mGy; P = 0.011). Exposure of radiation-sensitive organs such as colon (P = 0.015) and red bone marrow (P = 0.049) were also lower using the camera. Conclusions The introduction of a 3D camera improves patient positioning in the isocenter of the scanner, which results in a lower and also better balanced dose reduction for the patients.
CRIS-Team Scopus Importer:2023-01-27
Keywords: diagnostic imaging; patient-centering; radiation dosage